2017
DOI: 10.1016/j.celrep.2016.12.090
|View full text |Cite
|
Sign up to set email alerts
|

PINK1 Primes Parkin-Mediated Ubiquitination of PARIS in Dopaminergic Neuronal Survival

Abstract: Mutations in PTEN-induced putative kinase 1 (PINK1) and parkin cause autosomal-recessive Parkinson’s disease through a common pathway involving mitochondrial quality control. Parkin inactivation leads to accumulation of the parkin interacting substrate (PARIS, ZNF746) that plays an important role in dopamine cell loss through repression of proliferator-activated receptor gamma coactivator-1α (PGC-1α) promoter activity. Here we show that PARIS, links PINK1 and parkin in a common pathway that regulates dopaminer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
144
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(148 citation statements)
references
References 77 publications
4
144
0
Order By: Relevance
“…PINK1 is expressed in U2OS cells (McLelland et al, 2018) while PARKIN has not been detected (Durcan et al, 2014), so it is possible that stabilized PINK1 phosphorylates other substrates that control Arp2/3 complex activation. Candidates include the recently discovered PINK1 substrate Paris (Lee et al, 2017), or possibly direct phosphorylation of an NPF.…”
Section: Discussionmentioning
confidence: 99%
“…PINK1 is expressed in U2OS cells (McLelland et al, 2018) while PARKIN has not been detected (Durcan et al, 2014), so it is possible that stabilized PINK1 phosphorylates other substrates that control Arp2/3 complex activation. Candidates include the recently discovered PINK1 substrate Paris (Lee et al, 2017), or possibly direct phosphorylation of an NPF.…”
Section: Discussionmentioning
confidence: 99%
“…This was validated by analysis of postmortem SNpc tissue of PD patients, in which DA neurons displayed a reduction in PGC-1α levels as well as downstream effectors such as nuclear encoded components of the ETC (Shin et al, 2011). Recent studies indicate that PARIS is phosphorylated by PINK1 to regulates PARIS ubiquitination and clearance by parkin where it controls PGC-1α levels indicating that PARIS provides a link between parkin and PINK1 in the regulation of mitochondrial biogenesis (Lee et al, 2017). …”
Section: Common Pathways In Pd Pathogenesismentioning
confidence: 99%
“…Studies have found that knockdown of PARIS in adult conditional parkin KO mice rescues mitochondrial defects and neurodegeneration (Shin et al, 2011). PARIS seems to be particularly important in the PINK1 and parkin pathway of neurodegeneration in PD since a reduction in PARIS levels rescues the neurodegeneration in adult conditional PINK1 knockdown mice (Lee et al, 2017). Moreover, defects in mitochondrial biogenesis drive the loss of DA neurons since adult conditional parkin KO mice have primary defects in mitochondrial biogenesis in the absence of measurable defects in mitophagy, consistent with rescue of degeneration by reducing PARIS levels (Stevens et al, 2015).…”
Section: Therapeuticsmentioning
confidence: 99%
“…If this is the case, the conformational change must be specific to phospho-Ub binding and not to that induced by parkin phosphorylation, because we show that only phospho-Ub binding is important for parkin loss. Both events have been proposed to release parkin's Ubl domain from its interaction with the RING1 domain [45]- [47], [81], [116], and both have also been shown to facilitate the access of E2 ubiquitin-conjugating enzymes to parkin's E2 binding site [46], [74]. Accordingly, neither of these effects is likely to be the crucial conformational change involved in parkin degradation.…”
Section: Discussionmentioning
confidence: 99%